Semi analytical solution of MHD Non-aligned Stagnation-point flow of Nanofluid over a Stretching Surface in a Porous Medium with a Convective Boundary Condition (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The stagnation-point flow over a stretched surface is concerned in many industrial processes such as soft sheet extrusion, metal spinning, and paper production. On the account of these possible engineering applications, the study of stagnation-point flows has received a lot of attention. In the present paper, the non-aligned stagnation-point flow has found to be interesting and innovative in the analysis of viscous nanofluid over stretching surface with a convective boundary condition in presence of porous medium and magnetic effect. The suitable similarity transformation is utilized for the reduction of a set of governing equations, which are solved by using the differential transformation method (DTM) with the aid of MAPLE software. The effect of different physical parameters on flow is shown with the help of graphsThe skin friction, the Nusselt number, and Sherwood number are tabulated. Further, velocity, temperature, and nanoparticle volume fraction profiles are shown graphically and physical parameters are discussed. The comparison of the obtained results with a fourth-order Runge–Kutta–Fehlberg integration scheme with shooting technique is made.